2011
DOI: 10.2754/avb201180040391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amlodipine on bone metabolism in male albino Wistar rats

Abstract: Amlodipine (dihydropyridine-type calcium channel blocker) is a widely used agent for the treatment of hypertension in human and veterinary medicine but detailed information about its effects on bone metabolism are missing. Therefore, the aim of our study was to investigate the effect of amlodipine on bone metabolism in male albino Wistar rats. Amlodipine (0.3 mg/100 g body weight; gavage) was administered to 8 rats for 8 weeks. Control group (n = 8) received aqua pro inj. (0.2 ml/100 g body weight; gavage). Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
6
6
0
Order By: Relevance
“…These results are consistent with other studies which concluded that to a certain extent, statins inhibit bone resorption and promote bone formation, but have no significant effect on bone mineral density in healthy rats [37,38]. In osteoporotic bone, studied by analysis of histological images and 1 H NMR relaxometry, both treatments showed a positive effect by increasing the percentage of femoral diaphysis trabecular bone.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with other studies which concluded that to a certain extent, statins inhibit bone resorption and promote bone formation, but have no significant effect on bone mineral density in healthy rats [37,38]. In osteoporotic bone, studied by analysis of histological images and 1 H NMR relaxometry, both treatments showed a positive effect by increasing the percentage of femoral diaphysis trabecular bone.…”
Section: Discussionsupporting
confidence: 92%
“…The ORX + AML rats had a higher concentration of BALP compared to that of the SHAM group, but rather less than that of the ORX group. These results are again in agreement with experiments carried out on normotensive Wistar rats [26]. We consider that AML affects the metabolism of osteoblasts by reduction of phosphatase activity in bone tissues.…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study are similar to those of a previous study with Wistar rats, in which AML induces the suppression of bone turnover, in particular by decreasing osteoformation, and to a lesser extent osteoresorption [26]. In SHR, AML decreases bone turnover, specifically by the modification of osteoformation and depression of osteoresorption.…”
Section: Discussionsupporting
confidence: 80%
“…These methods were described in detail in our previous report [14] . Prior to testing, the diameter of the midshaft of the femurs and the length from the top of the femur head to the distal point of the medial condyle were measured.…”
Section: Biomechanical Testing Proceduresmentioning
confidence: 99%